Effect of Process-Based Multi-Task Cognitive Training Program on Executive Function in Older Adults With Mild Cognitive Impairment: Study Rationale and Protocol Design for a Randomized Controlled Trial - Zhao, Xia; Wang, Lina; Ge, Chenxi; Liu, Xiaoshen; Chen, Mei; Zhang, Chen (Frontiers in Psychiatry, 2020)
Introduction: Recent research from both human and animal studies confirms that cognitive training gains a considerable effect on multiple cognitive domains in individuals with mild cognitive impairment. Previous studies have yet paid scant attention to executive function training. Little is known about whether this specific benefit translates to maintaining long-term effectiveness and transfer effects are. This study is designed as an effort to address this issue. Objective: The program aimed to evaluate the effect of process-based multi-task cognitive training on executive function and further explore its long-term effects and transfer effects in community elderly with MCI. Furthermore, we will explore the neural correlates latent the changed performances underlying the cognitive intervention. Methods: This program is a single-blinded, randomized, prospective clinical trial to test the effect of process-based multi-task cognitive training in community elderly with MCI. Ninety participants with MCI will be recruited and randomly assigned to the cognitive training group (n=45) and the wait-list control group (n=45). The cognitive training group will receive 10 weeks of process-based multi-task cognitive training and health education twice a week, at 40~60 minutes per session. While the wait-list control group will only receive 10 weeks of health education during the research period. The effect is measured using the executive function, neuropsychological assessment performance and related brain activity assessed with electroencephalogram parameters (slowness and complexity of the EEG) at baseline, after 10 weeks of training, and a 3-month follow-up. Results: The study is currently ongoing. Recruitment began in March 2019 and will conclude in June 2020. Effects of the process-based multi-task cognitive training on executive function in community elderly with MCI will be described in intention-to-treat analysis and protocol set principle. We will also explore the potential long-term effects and transfer effects. Discussion: If a process-based multi-task cognitive training program results in positive changes to executive function in community elderly with MCI, this might provide a viable and potential approach to delay the cognitive decline.